Dutch Sources on South Asia c. 1600-1825 (Volume 6) : Between Colombo and the Cape. Letters in Tamil, Dutch and Sinhala, Sent to Nicolaas Ondaatje from Ceylon, Exile at the Cape of Good Hope (1738-1737) - Tieken, Herman, (Brill | Manohar Publishers & Distributors, 2015)
In 1728, the Ceylonese Chettiyar Nicolaas Ondaatje was sent into exile to the Cape of Good Hope where he died in 1737, only a few months before the end of his term. All these years Nicolaas Ondaatje kept in contact with his family and friends in Ceylon through letters in Tamil, Dutch and Sinhala. His own letters are lost but those he received have been preserved. These letters give an intimate picture of an early eighteenth-century elite Chettiyar community in Ceylon employed by the Dutch East India Company. By contrast, at the Cape Nicolaas Ondaatje found himself in the company of the Free Blacks at the very bottom of the social ladder. Though as a convict he was allowed to move about freely, Ondaatje had to provide his own source of income, making a modest living, first as a doctor and trader and later as a home teacher. In the letters, which are kept in the archive in Cape Town, we have chanced upon a classic case of subaltern history. Here we have a protagonist who has been denied a voice by the quirk of the availability of historical documents, but whose situation comes through in the concern his family and friends show for him in exile thousands of miles away, over nine long years. The letters give an excellent picture of the loyalty of the Chettiyars to one of their own, of their unfailing Christian faith, and of their meticulous account keeping. That we will never know what Nicolaas Ondaatje did to deserve his long exile or how he died shortly before his term ended makes his life history all the more poignant.